2008
DOI: 10.4049/jimmunol.181.2.1019
|View full text |Cite
|
Sign up to set email alerts
|

ICOS Costimulation Expands Th2 Immunity by Augmenting Migration of Lymphocytes to Draining Lymph Nodes

Abstract: The T cell costimulatory molecule ICOS regulates Th2 effector function in allergic airway disease. Recently, several studies with ICOS−/− mice have also demonstrated a role for ICOS in Th2 differentiation. To determine the effects of ICOS on the early immune response, we investigated augmenting ICOS costimulation in a Th2-mediated immune response to Schistosoma mansoni Ags. We found that augmenting ICOS costimulation with B7RP-1-Fc increased the accumulation of T and B cells in the draining lymph nodes postimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…33 Another study showed that transfer of ICOSenriched T cells followed by allergen airway challenge induced infiltration of recipient lymphocytes. 34 Therefore, ICOS-ICOSL signaling is likely important for lymphocyte migration, although direct effects of ICOS on lymphocyte chemotaxis have not yet been examined.…”
Section: 32mentioning
confidence: 99%
“…33 Another study showed that transfer of ICOSenriched T cells followed by allergen airway challenge induced infiltration of recipient lymphocytes. 34 Therefore, ICOS-ICOSL signaling is likely important for lymphocyte migration, although direct effects of ICOS on lymphocyte chemotaxis have not yet been examined.…”
Section: 32mentioning
confidence: 99%
“…Furthermore, this costimulatory molecule has been suggested not only to intensify some of the functions of CD28 during an already established immune response but also to induce additional T-effector cell functions [22]. Recent studies suggest that ICOS-mediated costimulation may regulate TH2-effector cell function without affecting TH2 differentiation [23]. Another study showed that transfer of ICOS-enriched T cells followed by allergen airway challenge induced infiltration of recipient T and B cells as well as local production of allergen-specific IgE by intrapulmonary plasma cells [24].…”
Section: Involvement Of the B7:cd28 Family Molecules In The Regulatiomentioning
confidence: 99%
“…Therefore, we tested two co-stimulatory molecules -GITR and ICOSL -that can potentially shape NKT-cell responses. GITR had been shown previously to be essential for activation of NKT cells [18], while ICOSL can stimulate CD41 T cells to secrete IL-4 rather than 31].When a blocking anti-GITR antibody was added to the co-cultures of NKT cells with either MZ B cells or cDCs sensitized by aGalCer, NKT-cell proliferation and IL-4 production were not inhibited ( Fig. 6A and C).…”
mentioning
confidence: 82%
“…ICOS/ICOSL interaction was shown to have a major role on the expansion of T H 2 responses [23,31]. In vivo blockade of ICOS affects T H 2 effector functions [31,40] and the presence of a functional ICOS/ICOSL pathway was shown to be crucial for the development of T H 2-driven allergic airway disease and the development of allergen-specific T H 2 cells [23,31]. Moreover, T cells isolated from ICOS À/À mice were not able to produce IL-4 [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation